SPE Annual Technical Conference and Exhibition 2015
DOI: 10.2118/175118-ms
|View full text |Cite
|
Sign up to set email alerts
|

Direct Observation of the Impact of Nanopore Confinement on Petroleum Gas Condensation

Abstract: Condensation of petroleum retrograde gas and especially that around a wellbore can decrease the deliverability of the well significantly. Better estimation of the point of phase transition is the key for reservoir engineers to devise management strategies to reduce condensate dropout and improve production and ultimate recovery. It has been established theoretically that the point of phase transition obtained from bulk PVT experiments does not represent the phase behavior of hydrocarbon fluids confined in nano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 9 publications
0
11
0
Order By: Relevance
“…Ally et al studied the phase behavior of propane and carbon dioxide using a colloidal crystal packed bed and demonstrated that the capillary condensation depends on the pore geometry and pore radius. Parsa et al directly observed the phase behavior of propane in nanopores and showed that confinement caused gas-phase condensation to occur at much lower pressures. Luo et al used differential scanning calorimetry to measure the large difference in bubble points of hydrocarbon fluids in controlled pore glasses with different pore radiuses and found that confinement causes a significant change in fluid behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Ally et al studied the phase behavior of propane and carbon dioxide using a colloidal crystal packed bed and demonstrated that the capillary condensation depends on the pore geometry and pore radius. Parsa et al directly observed the phase behavior of propane in nanopores and showed that confinement caused gas-phase condensation to occur at much lower pressures. Luo et al used differential scanning calorimetry to measure the large difference in bubble points of hydrocarbon fluids in controlled pore glasses with different pore radiuses and found that confinement causes a significant change in fluid behavior.…”
Section: Introductionmentioning
confidence: 99%
“…The confined bubble point pressure and critical temperature are lower, and the deviation from the bulk values increases as the depth of the nanochannels lowers or the confinement effect is elevated. The dew point deviation is not yet thoroughly known due to experimental data deficiency, on the one hand, and the differences between the real shale core and porous materials used in the lab experiments on the other hand. , …”
Section: Introductionmentioning
confidence: 99%
“…The dew point deviation is not yet thoroughly known due to experimental data deficiency, on the one hand, and the differences between the real shale core and porous materials used in the lab experiments on the other hand. 25,26 Despite the fact that lab experiments provide visual evidence for the phase behavior of the confined fluid, they are expensive and cover a limited range of fluid type, pressure, and temperature. Molecular simulation, on the other hand, does not suffer from such constraints and solves the molecular system for position and momentum distribution.…”
Section: Introductionmentioning
confidence: 99%
“…Experimentally, the adsorption isotherm relates the amount of fluid adsorbed on mesoporous pores (MCM-41, SBA-15, and controlled pore glass) to the operating bulk pressure at a given temperature . The capillary condensation pressure is generally identified as the midpoint of the step change in the adsorption isotherm branch. , Meanwhile, the microfluidic chip and the differential scanning calorimetry method have also been applied to obtain the capillary condensation pressure in nanopores, mainly for single-component fluids. As for the statistical thermodynamic simulation, the capillary condensation pressures of cylindrical nanopores with various pore sizes from 2 to 4 nm were determined by Miyahara et al via a molecular dynamic technique.…”
Section: Introductionmentioning
confidence: 99%